Monitoring and diagnosis of viral infections in Cucurbitaceae plants in Ukraine - Tsvihun, V.; Levishko, A.; Gumeniuk, I.; Sherstoboeva, O. (Quarantine and plant protection, 2025)
Goal. To investigate the species composition and incidence of viral infections in plants of the Cucurbitaceae family in Ukraine, and to identify the possible etiology of their origin. Methods. A range of methods was used in this study, including visual diagnosis, enzyme-linked immunosorbent assay (ELISA) in both indirect and sandwich modifications, electron microscopy, and statistical data analysis. Results. During the study, viral diseases of Cucurbitaceae crops in Ukraine were analyzed based on symptoms. Examination of collected plant samples from the Cucurbitaceae family revealed that 59% of symptomatic specimens were contaminated with viruses. The Cucumber mosaic virus (CMV) antigen was detected in 18% of affected plants, both as a mono-infection and in mixed infections with Watermelon mosaic virus 2 (WMV-2) and Zucchini yellow mosaic virus (ZYMV). The seed transmission pathway of vegetable crop viruses in Ukraine was demonstrated as one of the sources of viral presence in agroecosystems. It was established that CMV is the most hazardous among the identified viruses, with a wide range of host plants and confirmed presence in seeds. Conclusions. As a result of visual diagnostics of plants from the Cucurbitaceae family, various types of virus-like symptoms were observed. Using ELISA, 203 collected plant samples were tested, and 91 samples showed positive results for CMV, WMV-2, and ZYMV. Seed material from 18 Cucurbitaceae cultivars was also examined. ELISA testing of the seed material revealed that 30.5% of the tested samples were contaminated with viruses. The presence of CMV and ZYMV antigens was detected. Viral antigens were identified in cucumber cultivars ‘Kushchovyi’, ‘Zasolochnyi’, and ‘Dalekoskhidnyi’; zucchini cultivars ‘Iskander F1’ and ‘Hrybovskyi’; watermelon cultivar ‘Bochka Medu’; and melon cultivar ‘Medovyi Aromat’.